Adaptive KV Cache Management for Efficient Transformer-based LLM Inference - Leveraging Attention Sparsity for Memory Optimization - Xu, Dikai (My University, 2025)
This Master’s thesis addresses the critical challenge of memory inefficiency in Transformerbased Large Language Models (LLMs) during inference, specifically focusing on the prohibitive memory footprint of the Key-Value (KV) cache. As LLMs scale, the KV cache becomes a significant bottleneck, limiting longer context windows and overall operational efficiency. To mitigate this issue, we propose and evaluate Adap-KV, a novel adaptive memory management strategy for the KV cache. Adap-KV employs a layer-aware dynamic allocation approach that intelligently adjusts KV cache size in real-time, leveraging insights from attention sparsity patterns. Our method aims to optimize memory utilization without compromising the performance or quality of LLM inference. Experimental results demonstrate that Adap-KV significantly reduces KV cache memory consumption, thereby enhancing the efficiency and scalability of Transformer-based LLMs, making them more amenable for real-world deployments with extended context capabilities.
Keywords: Large Language Models; Transformers; KV Cache; Memory Optimization; Adaptive Memory Management; Attention Sparsity; Deep Learning Inference; Resource Efficiency